2020
DOI: 10.3389/fcell.2020.00722
|View full text |Cite
|
Sign up to set email alerts
|

Olfactomedin-3 Enhances Seizure Activity by Interacting With AMPA Receptors in Epilepsy Models

Abstract: Background: OLFM3 (olfactomedin-3) is a member of the olfactomedin domain family, which has been found to stimulate the formation and adhesion of tight cell connections and to regulate cytoskeleton formation and cell migration. Differences in the gene coding for OLFM3 have been found between patients with epilepsy and controls. However, the exact role of OLFM3 in epilepsy has not been thoroughly investigated. Methods: Biochemical methods were used to assess OLFM3 expression and localization in the cortex of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“… 36 The olfactomedin structural domain family protein OLFM3, which is present in neurons, promotes the formation of tight junctions. 37 An increased risk of ASD is associated with disruption of the tight junctions, one of the vital components of the blood–brain barrier (BBB). 38 SLC27A4, with the highest AUC value among the genes negatively associated with ZIC1, is a member of the fatty acid transport family of proteins involved in the translocation of fatty acids across the BBB.…”
Section: Discussionmentioning
confidence: 99%
“… 36 The olfactomedin structural domain family protein OLFM3, which is present in neurons, promotes the formation of tight junctions. 37 An increased risk of ASD is associated with disruption of the tight junctions, one of the vital components of the blood–brain barrier (BBB). 38 SLC27A4, with the highest AUC value among the genes negatively associated with ZIC1, is a member of the fatty acid transport family of proteins involved in the translocation of fatty acids across the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [62], Kowalczyk et al [63] and Sun et al [64] revealed that the expression of ADCYAP1, NPAS4, NPSR1, HTR2C, GABRB2, ALOX12B, ADRB3, EGR3, HSPA1A and IL3RA are associated with progression of schizophrenia, but these genes might be novel target for AD. GABRA6 [65], GABRA1 [66], GABRG2 [67], SLC4A10 [68], HCN1 [69], GABRA4 [70], KCNC2 [71], SCN2A [72], SYN2 [73], FGF12 [74], SCN8A [75], OLFM3 [76], PLCB1 [77], KCNQ5 [78], TUBB2A [79], SIK1 [80], ABCC2 [81], SLC6A12 [82] and COL6A2 [83] have been reported to be closely related to the occurrence and development of epilepsy, but these genes might be novel target for AD. Previous investigation demonstrates that RGS4 [84] [92], NRN1 [93], SYT1 [94], GRIN2B [95], AVP (arginine vasopressin) [96], VSNL1 [97], HTR2A [98], PAK3 [99] [108], IGF1 [109], PLK2 [110], CBLN4 [111], CAP2 [112], SV2B [113], CAMK4 [114], INA (internexin neuronal intermediate filament protein alpha) [115] KIF5A [179] are associated with amyotrophic lateral sclerosis, but these genes might be novel target for AD.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuzaki et al [55], Shepard et al [56], Lennertz et al [57], Klemettilä et al [58], Ullah et al [59], Kim et al [60], Sasayama et al [61], Li et al [62], Kowalczyk et al [63] and Sun et al [64] revealed that the expression of ADCYAP1, NPAS4, NPSR1, HTR2C, GABRB2, ALOX12B, ADRB3, EGR3, HSPA1A and IL3RA are associated with progression of schizophrenia, but these genes might be novel target for AD. GABRA6 [65], GABRA1 [66], GABRG2 [67], SLC4A10 [68], HCN1 [69], GABRA4 [70], KCNC2 [71], SCN2A [72], SYN2 [73], FGF12 [74], SCN8A [75], OLFM3 [76], PLCB1 [77], KCNQ5 [78], TUBB2A [79], SIK1 [80], ABCC2 [81], SLC6A12 [82] and COL6A2 [83] have been reported to be closely related to the occurrence and development of epilepsy, but these genes might be novel target for AD. Previous investigation demonstrates that RGS4 [84], CXCL11 [85], EGR1 [86], CALB1 [87], BDNF (brain derived neurotrophic factor) [88], TERT (telomerase reverse transcriptase) [89], NEFL (neurofilament light) [90], SNAP25 [91], RPH3A [92], NRN1 [93], SYT1 [94], GRIN2B [95], AVP (arginine vasopressin) [96], VSNL1 [97], HTR2A [98], PAK3 [99], STXBP5L [100], HCRTR2 [101], SYP (synaptophysin) [102], SYT10 [103], PRKCE (protein kinase C epsilon) [104], NRG1 [105], KISS1 [106], NRXN3 [107], RAB3A [108], IGF1 [109], PLK2 [110], CBLN4 [111], CAP2 [112], SV2B [113], CAMK4 [114], INA (internexin neuronal intermediate filament protein alpha) [115], GAP43 [116], TTR (transthyretin) [117], CXCR2 [118], IL1R2 [119], CXCR4 [120], CCR2 [121], MYOCD (myocardin) [122], S100A12 […”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation